1994
DOI: 10.1159/000126786
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Adenyl Cyclase-Activating Peptide: A Hypophysiotropic Factor That Stimulates Proopiomelanocortin Gene Transcription, and Proopio-melanocortin-Derived Peptide Secretion in Corticotropic Cells

Abstract: The biological effects of pituitary adenylate cyclase-activating peptide (PACAP) 27 and 38 on peptide secretion and gene regulation were studied in the mouse corticotrope-derived cell line AtT20. Treatment of these cells with PACAP 27/38 led to a dose-dependent increase in cAMP content and ACTH accumulation in the medium with an apparent ED50 value close to 10–9M The genomic effects of PACAP were first investigated by using a reporter gene containing a cAMP responsive element (CRE: TGACGT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 32 publications
2
14
1
Order By: Relevance
“…Similar mechanisms have been reported with the somatolactotrope GH4C1 cell line, in which PACAP activates PRL gene expression through VPAC2-R in a cAMP/PKA/ERK/Rap1-dependent manner (Le Péchon-Vallée et al, 2000;Romano et al, 2003). In the corticotrope AtT20 cell line, PACAP mimics the effect of CRH; i.e., it stimulates AC activity and triggers both POMC gene transcription and adrenocorticotropin release Lutz-Bucher, 1992a, 1995;Boutillier et al, 1994;Braas et al, 1994;Aoki et al, 1997). In the folliculostellate cell line TtT/GF, PACAP increases IL-6 secretion .…”
Section: Effects Of Pituitary Adenylate Cyclase-activating Polypepsupporting
confidence: 55%
“…Similar mechanisms have been reported with the somatolactotrope GH4C1 cell line, in which PACAP activates PRL gene expression through VPAC2-R in a cAMP/PKA/ERK/Rap1-dependent manner (Le Péchon-Vallée et al, 2000;Romano et al, 2003). In the corticotrope AtT20 cell line, PACAP mimics the effect of CRH; i.e., it stimulates AC activity and triggers both POMC gene transcription and adrenocorticotropin release Lutz-Bucher, 1992a, 1995;Boutillier et al, 1994;Braas et al, 1994;Aoki et al, 1997). In the folliculostellate cell line TtT/GF, PACAP increases IL-6 secretion .…”
Section: Effects Of Pituitary Adenylate Cyclase-activating Polypepsupporting
confidence: 55%
“…PACAP also stimulates cAMP production in the AP. PACAP, therefore, could regulate pituitary corticotrophs directly (Boutillier et al 1994). CRF and AVP neurons in the parvocellular region of PVN project to the external zone of the ME (Seasholtz et al 1988, Gonzalez-Hernandez et al 2006.…”
Section: Discussionmentioning
confidence: 99%
“…PACAP also increases CRF mRNA levels in the parvocellular region of the PVN, suggesting that PACAP is involved in the positive regulation of CRF gene expression (Grinevich et al 1997). Therefore, it is suggested that PACAP might regulate the HPA axis by stimulation of CRF gene expression in the hypothalamus and through direct effects on pituitary corticotrophs (Boutillier et al 1994, Aoki et al 1997, Agarwal et al 2005. PACAP also activates AVP neurons of the PVN or SON via PAC1 receptor (Shioda et al 1997b, Nomura et al 1999.…”
Section: Introductionmentioning
confidence: 99%
“…4) and through direct effects on pituitary corticotrophs [14,16,17]. PaCaP also stimulates both arginine vasopressin (aVP) gene transcription and mRNa expression via the camP-PKa pathway in hypothalamic 4B cells (Fig.…”
Section: Involvement Of Camp On Crf Gene Transcriptionmentioning
confidence: 99%